A psychotic experience during adolescence: reasoning about differential diagnosis. Case report - Leite, Vítor Ferreira; Araújo, Carla Andrade (São Paulo Medical Journal, 2018)
CONTEXT: The aim of the present clinical review was to illustrate the diagnostic difficulty associated with psychotic experiences during adolescence, in the light of the multiplicity of circumstances interplaying during this period. It was also intended to illustrate the observation that not all hallucinations occur in the context of a declared psychotic disorder. CASE REPORT: The patient was a 16-year-old adolescent girl who came to the Emergency Department of Coimbra Pediatric Hospital. On admission, she displayed mood and sensory perception disorders, with a bizarre gait abnormality. A diagnosis of conversion disorder was finally suggested, in accordance with the International Classification of Diseases, 10th edition. CONCLUSIONS: Conversive hallucinations are rare in the psychiatric literature. This diagnostic hypothesis only gained consistency over a long period of follow-up within a child and adolescent psychiatry outpa- tient service, which was fundamental for appropriate diagnostic clarification. The authors discuss psychotic experiences that can arise from a neurotic setting and share the reasoning that was constructed in relation to the differential diagnosis. The psychogenesis and phenomenology of this young patient’s conversive hallucinations and the therapeutic strategies adopted over the course of the follow-up are also discussed.